Serum IL-1beta, IL-6, IL-8, and TNF-alpha levels in early diagnosis and management of neonatal sepsis. - Kurt, A Nese Citak; Aygun, A Denizmen; Godekmerdan, Ahmet; Dogan, Yasar; Yilmaz, Erdal (My University, 2007)
AIM: To determine serum IL-1beta, IL-6, IL-8, and TNF-alpha levels in neonatal sepsis at the time of diagnosis and after therapy, and to show the meaningful on the follow up. METHODS: This prospective study was performed on newborns who were hospitalized for neonatal sepsis and who were classified as culture-proven sepsis (n=12), as culture-negative sepsis (n=21), and as healthy newborns (n=17). RESULTS: At the time of diagnosis, serum IL-1beta, IL-6, IL-8, and TNF-alpha levels of culture-proven sepsis were significantly higher than those of the control groups (P<.05). At the time of diagnosis, IL-1beta, IL-6, IL-8, and TNF-alpha levels of culture-proven sepsis and culture-negative sepsis were significantly higher than levels at the seventh day after antibiotic treatment. CONCLUSION: Serum IL-1beta, IL-6, IL-8, and TNF-alpha are mediators of inflammation and can be used at the diagnosis and at the evaluation of the therapeutic efficiency in neonatal sepsis.
Keywords: Anti-Bacterial Agents; Anti-Infective Agents; Chemotaxis; Female; Gene Expression Regulation; Humans; Infant, Newborn; Inflammation; Interleukin-1beta; Interleukin-6; Interleukin-8; Male; Prospective Studies; Sepsis; Tumor Necrosis Factor-alpha; antiinfective agent; interleukin 1beta; interleukin 6; interleukin 8; tumor necrosis factor alpha; article; blood; chemotaxis; female; gene expression regulation; human; inflammation; male; newborn; prospective study; sepsis